2020
DOI: 10.1186/s41235-020-00245-2
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty promotes information-seeking actions, but what information?

Abstract: Navigating an unfamiliar city almost certainly brings out uncertainty about getting from place to place. This uncertainty, in turn, triggers information gathering. While navigational uncertainty is common, little is known about what type of information people seek when they are uncertain. The primary choices for information types with environments include landmarks (distal or local), landmark configurations (relation between two or more landmarks), and a distinct geometry, at least for some environments. Uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 110 publications
(159 reference statements)
1
16
0
Order By: Relevance
“…Although information-gathering has won less academic attention than information-seeking (the most commonly used term, yet with limited applicability; Case and Given, 2016: 93), both concepts concern the flow of information to a person in context (see Paisley, 1965). However, the study of information-gathering behaviour expands the scope of knowledge and discourse along the mere self-search for information (Keller et al, 2020), and beyond, to additional strategies, habits and experiences of gaining available information. It thus provides a broader perspective that adheres better to professionals’ work-related reality and desired skills.…”
Section: Introductionmentioning
confidence: 99%
“…Although information-gathering has won less academic attention than information-seeking (the most commonly used term, yet with limited applicability; Case and Given, 2016: 93), both concepts concern the flow of information to a person in context (see Paisley, 1965). However, the study of information-gathering behaviour expands the scope of knowledge and discourse along the mere self-search for information (Keller et al, 2020), and beyond, to additional strategies, habits and experiences of gaining available information. It thus provides a broader perspective that adheres better to professionals’ work-related reality and desired skills.…”
Section: Introductionmentioning
confidence: 99%
“…Properly defining disorientation and testing for its presence in Twitter signals is a main task of this article. A preliminary literature search on the subject suggested that the issue of "disorientation", though ubiquitously present in many disciplines such as medical and cognitive sciences, spatial and information sciences, and social science [29][30][31], does not seem to have received systematic attention in the literature on information, opinions and online social media. Generally speaking, "disorientation" can be simply a consequence of the lack of adequate information, of the over-exposition to information, including misinformation, and more generally, of information disorder [32].…”
Section: Introductionmentioning
confidence: 99%
“…Dedeoglu and Ventura (2017) showed that in response to the fear of the swine flu news, people would collect information from scientific sources to alleviate the fear emotion and to improve rational responses. Moreover, dreadful rumors associated with the fear emotion imply possible risks or uncertainties that would drive people to seek factual knowledge of information to help with their coping strategies (Keller et al, 2020;Chowdhury et al, 2011). Past research has shown that the fear appeal would elicit appraisals of uncertainty and situational controls (Lerner et al, 2003;Roskos-Ewoldsen et al, 2004).…”
Section: Dreadfulnessmentioning
confidence: 99%
“…The fear-arousing stimuli can lead people to perceive threat (Roskos-Ewoldsen et al, 2004) and uncertainty (Lerner et al, 2003). The risk and/or uncertainty perception, in turn, would drive people to seek information or factual knowledge to help reduce the risky or uncertain perception and to make decisions (Keller et al, 2020;Chowdhury et al, 2011) and/or to engage in the danger control process (Roskos-Ewoldsen et al, 2004) by collecting factual knowledge to improve rational responses (Dedeoglu and Ventura, 2017). In sum, upon facing risks or uncertainties, people would seek information that would help with their decisions.…”
Section: Dreadfulnessmentioning
confidence: 99%